Seeing IR differently: notes from the third world (2003)
This article explores the importance of distinct non-core and non-Western perspectives for critical interpretations of international relations. A series of arguments are offered as to why third world scholarship is invisible within the field, and why features such as culture, everyday life and hydridity make looking at IR from third world loci of enunciation fundamentally different. In order to observe the ways in which such readings complement and refine prevailing understandings of global politics, the article reexamines several key categories, including war and conflict, the state, sovereignty and autonomy, and nationalism, making use of distinct third world perspectives.